Diseño arquitectónico de prototipos de vivienda rural de la ciudad de Babahoyo - Veletanga Meléndez, Kevin Alexander (2024)
The sustainable and ecological process is very important when establishing the integration of the inhabitants and meeting needs. In the project "Architectural design of rural housing prototypes in the city of Babahoyo" throughout the development it was possible to obtain the main needs of the place, for the construction of buildings resistant to climatic factors and that these at the same time can be adapted to any change in climate. Although in the Febres Cordero parish, in the Babahoyo canton, province of Los Ríos, there are homes that meet the needs of families, but they are in a state of low performance, failing to meet the objectives that they want to implement for a prototype. of very resistant housing, this being a point in the population where the trust and security of the inhabitants has been becoming a setback, increasing a risk for families, both in the home and in food............